Intervention for Prevention of Type 2 Diabetes Mellitus Among Prediabetes: A Review of the Literature - Sopida Thipsawat MNS (SAGE Publishing, 2023)
Introduction In recent decades, the prevalence and incidence of type 2 diabetes mellitus (T2DM) have increased rapidly and represent a significant public health problem worldwide. Long-term T2DM is associated with microvascular complications such as retinopathy, nephropathy, and neuropathy. Prediabetes is a state of hyperglycemia with blood glucose levels higher than normal but lower than the diabetes threshold. Several studies have demonstrated the effectiveness of lifestyle interventions that resulted in a 40% to 70% reduction in diabetes mellitus in adults with prediabetes. These interventions focused on increased physical activity and dietary changes that were able to prevent or delay the onset of T2DM in prediabetes. However, most review studies focused on interventions to prevent T2DM in high-risk groups such as obesity. There was a limitation of reports related to prediabetes. Nevertheless, it remains a high-risk condition for the development of T2DM with a conversion rate of 5% to 10% per year. Therefore, the aim of this study was to review the current evidence on intervention studies aimed at reducing the incidence of type 2 diabetes in prediabetes. Method The researcher conducted a literature search of common online databases such as Medline, Google Scholar, and Cochrane Library between January 2011 and December 2021. Result The intervention for the prevention of T2DM in prediabetes consisted of a lifestyle intervention, a nutritional supplementation intervention, and a pharmacological intervention Conclusion Several studies suggest that T2DM in prediabetes can be prevented by lifestyle modification and pharmacological interventions, or a combined intervention. However, further interventions may be needed to confirm this.